Student Perspectives on Dialogic Learning Communication at DIC Business School: Perspektif Mahasiswa tentang Komunikasi Pembelajaran Dialogis di DIC Business School - Dewi Khotimah; Ainur Rochmania (Academia Open, 2025)
General Background: Contemporary education increasingly emphasizes learner-centered communication that supports critical thinking, creativity, and active participation in response to dynamic social and professional demands. Specific Background: Dialogic, democratic, and praxis-oriented learning communication, as articulated in critical pedagogical traditions, seeks to connect theoretical knowledge with real-life and vocational contexts. Knowledge Gap: While dialogic learning communication is widely discussed conceptually, there is limited qualitative evidence describing how students perceive and experience such practices within vocational higher education institutions. Aims: This study aimed to describe student opinions on learning communication implemented at DIC Business School Sidoarjo. Results: Employing a qualitative descriptive approach through in-depth interviews with students and key informants, the findings show that learning communication at DIC Business School is dialogic and critical, encouraging open discussion, freedom of expression, collaborative interaction, and the application of theory in daily life and the world of work. Novelty: The study offers a focused qualitative portrayal of student perspectives on dialogic and praxis-based learning communication within a vocational business school environment. Implications: These findings underscore the relevance of dialogic and praxis-oriented communication in fostering active engagement, reflective thinking, and collaborative learning, providing practical insights for the development of communicative learning practices in contemporary vocational education. Highlights: Learners Reported Active Classroom Discussions and Freedom to Express Viewpoints. Instruction Linked Theoretical Content With Everyday and Workplace Practice. Collaborative Interaction Supported Reflective and Participatory Learning Experiences. Keywords: Student Opinion, Learning Communication, Dialogic Learning, Critical Pedagogy, Vocational Education